Displaying environmental information to satisfy utility and sufficiency in entity reporting / Jeffrey Faux - Faux, Jeffrey (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
Entity reporting of environmental information may take many forms and assessing the utility and sufficiency of environmental reports could assist in determining which display formats provide greater usefulness to users for decision making. The utility and sufficiency of certain display formats were assessed in this study by providing three user groups (shareholders,shareholder/environmentalists and environmentalists) with a scenario(vignette) and one of four alternative report displays: monetary, statistical, narrative or pictorial. The preference by user groups for narrative disclosure and the deemed inadequacy of the display in terms of sufficiency were significant findings of this study.